PENGARUH INDEPENDENSI DAN PROFESIOANALISME AUDITOR TERHADAP KUALITAS AUDIT (STUDI KASUS PADA BANK PERKREDITAN RAKYAT DI KOTA PALEMBANG) - Mella Handayani (Universitas Tridinanti, 2022)
This study aims to examine the effect of auditor independence and professionalism on audit quality at Rural Banks in Palembang City. This research is a quantitative model, and the data analyzed is multiple linear regression. Data collection techniques were carried out through the distribution of questionnaires and interviews. The statistical method uses validity test, reliability test, classical assumption test and multiple linear regression analysis test using SPSS 25. The results of the study together with independence and professionalism of auditors have a significant effect on audit quality. Partially, it shows that independence has an effect on audit quality. Professionalism has an effect on audit quality.Keywords: Independence, Auditor Professionalism, Audit Quality